2005
DOI: 10.1073/pnas.0506081102
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific recombinase and integrase activities of a conjugative relaxase in recipient cells

Abstract: Conjugative relaxases are the proteins that initiate bacterial conjugation by a site-specific cleavage of the transferred DNA strand. In vitro, they show strand-transferase activity on single-stranded DNA, which suggests they may also be responsible for recircularization of the transferred DNA. In this work, we show that TrwC, the relaxase of plasmid R388, is fully functional in the recipient cell, as shown by complementation of an R388 trwC mutant in the recipient. TrwC transport to the recipient is also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 42 publications
5
141
1
1
Order By: Relevance
“…Single-tyrosine relaxases could achieve resolution of CPR intermediates through relaxase multimerization (45) or cooperation with a second nonrelaxase protein (46). The ability to resolve undesirable replication products would also confer oriT specific recombinase activity between plasmids (47,48) or between tandem oriT repeats on the same plasmid (46,49). However, for our purposes, a key prediction that arose from this model is that multityrosine relaxases are capable of accommodating two phosphotyrosine intermediates simultaneously within their active sites.…”
Section: Resultsmentioning
confidence: 93%
“…Single-tyrosine relaxases could achieve resolution of CPR intermediates through relaxase multimerization (45) or cooperation with a second nonrelaxase protein (46). The ability to resolve undesirable replication products would also confer oriT specific recombinase activity between plasmids (47,48) or between tandem oriT repeats on the same plasmid (46,49). However, for our purposes, a key prediction that arose from this model is that multityrosine relaxases are capable of accommodating two phosphotyrosine intermediates simultaneously within their active sites.…”
Section: Resultsmentioning
confidence: 93%
“…Where characterized, relaxases covalently bound to the 5Ј end of T strands carry C-terminal signals specifying DNA substrate-channel interactions. Moreover, several relaxases including MobA RSF1010 , VirD2 At , TraA pATC58 , and TrwC R388 are bona fide substrates of T4SS even without any associated DNA, as demonstrated by the Cre reporter assay for translocation (84,214,239,269). With this assay, it was also shown that the C-terminal 50 residues of MobA RSF1010 are sufficient to mediate Cre translocation (269).…”
Section: C-terminal Secretion Signalsmentioning
confidence: 93%
“…The relaxase also "pilots" the T strand through the translocation channel. In the recipient cell, the relaxase catalyzes the recircularization of the T strand and may also participate in second-strand synthesis or recombination into the chromosome (52,84,105).…”
Section: Conjugation Systemsmentioning
confidence: 99%
“…It is also thought to energize the process of DNA transport (135,136). The conjugative mating channel is basically a protein secretion channel, which transports the relaxase protein bound to the DNA to be transferred (43,58). According to the nomenclature of protein secretion mechanisms, it is a T4SS (54).…”
Section: General Properties Of Plasmid Mobilitymentioning
confidence: 99%